Hubungan Pengetahuan Tentang Keputihan dengan Perilaku Penggunaan Pantyliner pada Remaja Putri - Mita Wijayanti; Tri Susilowati (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Vaginal discharge is one of the most common problems faced by women, especially teenagers. The incidence of vaginal discharge in adolescent girls increases by 5% every year. This happens because of the lack of knowledge about vaginal discharge and cleanliness of reproductive organs and behavior that depends on the use of pantyliners. The Correlation analytic research with cross sectional approach. The technique in taking the sample is through purposive sampling, with a total sample of 83 respondents. The results of the univariate analysis showed that the level of knowledge about vaginal discharge in young women in Gondang Village was in the high category and the behavior of using pantyliners was in the positive category. Meanwhile, the results of the bivariate test prove that the level of knowledge about vaginal discharge is related to the behavior of using pantyliners in young women with p value = 0.000 < = 0.05. Level of knowledge about the whiteness of adolescent girls is in the high category with the behavior of using pantyliners in the positive category. There is a relationship between knowledge of vaginal discharge and the behavior of using pantyliners in adolescent girls aged 10-21 years in Gondang Village, Gondang District, Sragen Regency.